Morphosemantic Analysis Skills Among Digital Native Non-Arabic Speakers - Adawiah, Siti Robiatul; Sopian, Asep; Nursyamsiah, Nunung (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
This study aims to determine the ability of Arabic morphosemantic analysis on digital natives who are not native Arabic speakers. The research method used is descriptive quantitative with percentage-based analysis. Data were collected through an open-ended multiple-choice test that was structured based on morphosemantic indicators. The validity of the test instrument has been confirmed by Arabic morphosemantics experts. The study involved 34 digital native Arabic students, selected through a purposive sampling technique. The results show that the morphosemantic analysis ability of digital native non-Arabic speakers is generally considered insufficient, with a percentage of 49.2%. The ability in the aspects of word derivation and shighat is classified as moderate with a percentage of 67.6% and 65.7% respectively, while the ability in the aspects of affixes, word roots, semantic aspects, and wazan is categorized as